أثر اخلاقيات العمل على إدارة الصراع التنظيمي ـ دراسة حالة ـ - هاجر بسي; سناء بريك; خديجة بقاص (university of eloued جامعة الوادي, 2025)
هدفت هذه الدراسة الى التعرف اثر اخلاقيات العمل على ادارة الصراع التنظيمي في مدرية توزيع الكهرباء والغاز سونلغاز بالوادي حيث اعتمدت الدراسة على المنهج الوصفي التحليلي ودراسة حالة واستخدم الاستبيان والمقابلة كأداتين رئيسيتين لجمع المعلومات من عينة من موظفي المدرية حيث تم تحليل 50استبيان بإستخدام برنامج spss وتوصلت الدراسة الى نتائج ابرزها وجود اثر اجابي لإبعاد اخلاقيات العمل على ادارة الصراع التنظيمي لمدرية توزيع الكهرباء والغاز سونلغاز بالوادي، وكما انه لا توجد فروقات ذات دلالة إحصائية لإدارة الصراع التنظيمي تبعا للمتغيرات الديمغرافية (الجنس والعمر، المؤهل العلمي، سنوات الخبرة، المهنة.) في مديرية توزيع الكهرباء والغاز بالوادي وانه هناك مدونة لاخلقيات العمل يجب الالتزام بها والتحلي بها من طرف جميع العمال بالمديرية. This study aimed to indentify the impact of work ethics on organizational conflict managent at the electricity and Gaz distribution directorate "Sonelgaz" in El Oued province. The study adopted the descriptive analytical approche and case study methodology. A questionnaire and interviews were used as the main tools for data collection from a sample of the directorate's employees. A total of of 50 questionnaires were analyzed using spsssoftware. The study reached several finding most notably apositive impact of the dimensions of work ethics on organizational conflict management at the sonelgaz electricity and gas distribution directorate in el oued. It also found that there are no statistically significant differences in conflict management based on demographic variables, furthermore, there is a code of work ethics that all employees at Sonelgaz Eloued must adhere to and uphold.
Keywords: اخلاقيات العمل; إدارة الصراع التنظيمي; مديرية سونلغاز بالوادي; work ethics; organizational conflict managent; Sonelgaz directorate.